KKN-Tematik UGJ Kelompok 17 Desa Ciketak Melakukan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) untuk Pengembangan UMKM di Desa Ciketak melalui Seminar Digital Marketing - Rahmadi, Rahmadi; Fatmawati, Ayu; Hendryawan, Muhammad Rifqi; Alfisah, Najwa Min; Aisah, Siti; Fitriyani, Suci (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Thematic Community Service Program (KKN-T) implemented by Universitas Swadaya Gunung Jati (UGJ) with the theme “Mutual Cooperation to Build Villages” aims to empower village communities through activities that focus on improving local economic welfare. One of the main initiatives in this KKN-T is mentoring in creating a Business Identification Number (NIB) for micro, small, and medium enterprises (UMKM) in the village. This program is implemented with a spirit of mutual cooperation involving students, village officials, and the local community. The mentoring activity aims to provide an understanding of the importance of business legality through NIB as an initial step towards developing a more professional and sustainable business. The results of this program show an increase in the number of UMKM that have business legality in the village, which is expected to support local economic growth, access to government assistance, and expand the market. This activity also strengthens collaboration between universities and the community in an effort to build sustainable village economic independence.